Initial Assessment of β-Adrenoceptor-Activated Brown Adipose Tissue in Streptozotocin-Induced Type 1 Diabetes Rodent Model Using [F]Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography - Aparna Baranwal; M. Reza Mirbolooki; Jogeshwar Mukherjee (Molecular Imaging)
Metabolic activity of brown adipose tissue (BAT) is activated by β 3 -adrenoceptor agonists and norepinephrine transporter (NET) blockers and is measurable using [ 18 F]fluorodeoxyglucose ([ 18 F]FDG) positron emission tomography/computed tomography (PET/CT) in rats. Using the streptozotocin (STZ)-treated rat model of type 1 diabetes mellitus (T1DM), we investigated BAT activity in this rat model under fasting and nonfasting conditions using [ 18 F]FDG PET/CT. Drugs that enhance BAT activity may have a potential for therapeutic development in lowering blood sugar in insulin-resistant diabetes. Rats were rendered diabetic by administration of STZand confirmed by glucose measures. [ 18 F]FDG was injected in the rats (fasted or nonfasted) pretreated with either saline or β 3 -adrenoceptor agonist CL316,243 or the NET blocker atomoxetine for PET/CT scans. [ 18 F]FDG metabolic activity was computed as standard uptake values (SUVs) in interscapular brown adipose tissue (IBAT) and compared across the different drug treatment conditions. Blood glucose levels > 500 mg/dL were established for the STZ-treated diabetic rats. Under fasting conditions, average uptake of [ 18 F]FDG in the IBAT of STZ-treated diabetic rats was approximately 70% lower compared to that of normal rats. Both CL316,243 and atomoxetine activated IBAT in normal rats had an SUV > 5, whereas activation in STZ-treated rats was significantly lower. The agonist CL316,243 activated IBAT up to threefold compared to saline in the fasted STZ-treated rat. In the nonfasted rat, the IBAT activation was up by twofold by CL316243. Atomoxetine had a greater effect on lowering blood sugar levels compared to CL316,243 in the nonfasted rats. A significant reduction in metabolic activity was observed in the STZ-treated diabetic rodent model. Increased IBAT activity in the STZ-treated diabetic rat under nonfasted conditions using the β 3 -adrenoceptor agonist CL316,243 suggests a potential role of BAT in modulating blood sugar levels. Further studies are needed to evaluate the therapeutic role of β3-adrenoceptor agonists in insulin-resistant T1DM.